(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
Denture base is the part of a denture that rests on the foundation tissues and to which teeth areAttached. Denture base may be complete or partial used for the alteration of missing natural teeth.The most popular material utilized for the fabrication of dentures base is the poly (methylmethacrylate) (PMMA) because is distinguished by many characteristic. The remarkable clarity ofa methyl methacrylate resin, its relatively high strength and hardness, its color stability under allconditions of dental use, its insolubility in the mouth fluids, all of these properties combine toprovide an excellent material for the prosthetics denture (S. S Carmen, 2010 and R. K. Alla 2013).This survey illustrate the effect of particle size of powders and weight fraction of natural Bambooand Rice Husk powders on PMMA, with the selected size particles of (25?m and 75?m) andweight fraction (2, 4, 6 and 8wt. %), on compression strength and hardness, and these experiencewere accomplished at a temperature of laboratory. The results showed improved in the hardnessand compression with concentration rate of Rice Husk and Bamboo powders in compositesamples. Also, the highest values of compressive strength and hardness were (300MPa.) and (86)respectively for (PMMA-8%RH) and particle size (25 ?m).